Managerial culture in the post-pandemic context: An action-research on evolving relationships with external clients and internal stakeholders: An action-research on evolving relationships with external clients and internal stakeholders - Carollo, Giuseppe; D'Antona, Elisa; Pacelli, Flavio; Contessini, Valeria (Quaderni di Psicologia Clinica, 2025)
The aim of this article is to promote hypotheses regarding changes in organizational cultures in the post-pandemic context, starting from the challenges faced by managers, particularly those related to human resource management. We present a concise and theoretically based overview of recent research in this area to locate within this framework a discussion of our own study, conducted in 2022, aimed at investigating the managerial culture of 60 Italian managers. The managerial culture we identified appears to struggle in constructively interpreting empolyees’ expectations, as well as clients’. This difficulty is consistent, on the one hand, with a symbolic representation of motivation as an individual and idiosyncratic dimension that pre-exist the encounter with the organizational context; and, on the other hand, with the fear for the ongoing changes and the illusion that they can be ignored to preserve an order perceived as fragile. Finally, we present the report of an organizational intervention developed following the research, highlighting the demand by managers to conceive the critical aspects of their relationship with employees and to draw on this feedback to orient their relationship with clients.
Keywords: psychosocial intervention; managerial practices; employee motivation; soft skill; work culture